Modern Approaches to Mechanisms of Eruption of Permanent Teeth: Focus On Maxillary Canines and Diagnosis of Their Eruption Disorders (Literature Review) - Lykhota, К. М.; Yakush, О. Г. (Actual Dentistry, 2024)
Introduction. Teething is a physiological process that occurs in a sequence established by nature to perform one of the main functions: chewing. However, in some cases, this mechanism fails or is interrupted, resulting in the absence of a tooth or teeth, usually the upper canines, which are fundamental to the patient’s esthetic, harmonious smile and stomatogenic system. The harmony of the face is directly related to the presence of canines in the dental arch, which is important for a stable bite. The correct size, shape, and position of the maxillary canines play an important role in the smile’s beauty. In addition, the maxillary canines also have an important functional and gnathological significance: these teeth ensure the disocclusion of the lateral teeth during excursion movements Purpose: based on the analysis of literary sources, to determine the main modern approaches to the mechanisms of the eruption of permanent teeth, particularly upper permanent canines, and methods of diagnosing disorders of their eruption. Materials and methods. Information search and analysis of scientific sources was done using scientometric databases Web of Science, PubMed, and Google Scholar over the past 15 years. Conclusion. The analysis of literary sources proved that the study of canine eruption in children is a crucial aspect of dentistry due to the specific role of canines in the development of the maxillofacial system. Canines, as key elements in the chewing process and formation of a correct bite, are of critical importance for the functional and aesthetic development of the oral cavity. Since the timing of canine eruption can significantly affect the bite’s correctness and the development of surrounding teeth, their study is important for early diagnosis and correction of possible anomalies.